Proceedings ARQUEOLÓGICA 2.0 - 9th International Congress &Amp; 3rd GEORES - GEOmatics and pREServation 2021
DOI: 10.4995/arqueologica9.2021.12155
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Generation in Hbim Workflows for Slam-Based Data: Discussing Expectations on Suitability and Accuracy

Abstract: In the wide framework of Scan-to-BIM 3D modelling procedures, the complexity of the architectural heritage and its components is evidencing a gap of best practices and specification in the HBIM-modeling and thus it is requiring important considerations about the modelling strategies and protocols between the requested level of detail (LOD), the expect accuracy and above all the actual use-oriented requirements. Several works are largely focusing on developing workflows for traditional static LiDAR scanning sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, it has been validated in an outdoor environment. Sammartano et al (2021) focused on H-BIM (Historic) modeling procedures based on SLAM (Simultaneous Localization and Mapping) technologies, analyzing the geometries and investigating the GOG (grade of generation) from the point of view of time-cost balance. In all the just-mentioned cases, the surveying activities have been planned in advance, and the acquisition phases have been carried out in the best possible way; however, in this case, the learning-by-doing approach took precedence over the compliance and best execution of the data acquisitions, thus the results have to be considered from an educational perspective.…”
Section: Scan-to-bim Approaches Based On Mms Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been validated in an outdoor environment. Sammartano et al (2021) focused on H-BIM (Historic) modeling procedures based on SLAM (Simultaneous Localization and Mapping) technologies, analyzing the geometries and investigating the GOG (grade of generation) from the point of view of time-cost balance. In all the just-mentioned cases, the surveying activities have been planned in advance, and the acquisition phases have been carried out in the best possible way; however, in this case, the learning-by-doing approach took precedence over the compliance and best execution of the data acquisitions, thus the results have to be considered from an educational perspective.…”
Section: Scan-to-bim Approaches Based On Mms Surveymentioning
confidence: 99%
“…Through these point clouds, confirmed by the analysis of the deviations, it was possible to achieve results compatible with a representation scale of 1:200 and, only sometimes up to 1:100, in any case with the support of point clouds from UAVs and TLS. During this experience, we have not achieved the accuracies of (Sammartano et al, 2021), and we are aware that a best-planned acquisition path would have helped the final MMS point clouds, though it has to be considered that all the data acquisitions were performed with the students, to implement a learning-by-doing approach, thus obtaining the best result was not the main purpose of the activity.…”
Section: Vertex Selectionmentioning
confidence: 99%
“…These new devices are constantly evolving technologies that need to be assessed against more consolidated techniques such as photogrammetry and TLS. In literature we find different approaches to evaluate iMMS data both in indoor and in outdoor contexts (Nocerino et al, 2017;Chiabrando et al, 2018;Sammartano et al, 2021;Salgues et al, 2020). As regards spherical photogrammetry, in their studies Abate et al (2017) and Barazzetti et al (2018) demonstrate that accurate metric reconstructions can be achieved using low-cost sensors.…”
Section: Urban Mapping Fast Acquisition Techniquesmentioning
confidence: 99%
“…The accuracy evaluation dealt with the geometric features of the point clouds produced and their ability to describe reality. In particular, we followed the approach proposed by Sammartano et al (2021) and Tucci et al (2018). We conducted an analysis of the global accuracy of SFM and SLAM point clouds compared to TLS cloud.…”
Section: Accuracy Evaluationmentioning
confidence: 99%
“…When evaluating the accuracy of TLS, SfM, and SLAM sensors, usually the TLS is used as the reference scan and the other two are compared against it. Research has already demonstrated that point clouds generated by SfM have lower accuracy than those created by SLAM sensors [7,10,13], but some issues arise when these sensors are used outdoors. Dynamic environments make simultaneous localization and mapping harder and consequently increase the chance of errors [10,14,15].…”
Section: Introductionmentioning
confidence: 99%